Estimated glomerular filtration rate as an independent predictor of atherosclerotic vascular disease in older women - Lewis, J.; Lim, W.; Dhaliwal, Satvinder; Zhu, K.; Lim, E.; Thompson, P.; Prince, R. (BioMed Central Limited, 2012)
Estimated glomerular filtration rate (eGFR) levels have been shown to predict atherosclerotic vascular disease hospitalization and mortality. We sought to investigate the role of renal function in the prediction of 10-year atherosclerotic vascular hospitalization and deaths in an unselected population of elderly women in and compared these predictions to Framingham equations